Tactical Helicopter Transportation Planning for Offshore Personnel on the Norwegian Continental Shelf - Irina Gribkovskaia; Gaute Øiestad Slettemark (Logistics)
Background: In offshore energy logistics, contracted helicopters frequently transport personnel to and from offshore installations. Regular and efficient transportation is vital to maintain planned activities at the installations. We focus on tactical helicopter planning from a single heliport for a period of stable weekly transport demands in a heliport operating area on the Norwegian Continental Shelf (NCS). This results in the construction of a repetitive weekly flight program, integrating the selection of helicopter resources optimally matching demand with the generation of a weekly timetable of flights assigning them to start times. The purpose of our research is to develop optimisation-based weekly flight program planning algorithms for energy companies operating on the NCS. Methods: We present a developed two-step solution method sequentially generating possible flights and solving a flight-based integer programming model, and an iterative algorithm based on the decomposition of the flight-based model for the construction of cost-optimal weekly flight programs. Results: The developed algorithms were validated on the real instances from Equinor, the largest NCS energy operator. The decomposition-based algorithm was able to solve to optimality all tested instances, with up to 20 installations served from the heliport within less than 9 min. Conclusions: Equinor logistics planners have tested and verified that the developed flight-based model satisfies the goals and planning policies imposed on the NCS for integrated tactical helicopter planning. Considering the advantages of the decomposition-based algorithm performance in solution quality and speed, energy companies on the NCS find it well-suited as a solution engine in the highly demanded automated decision support tools for tactical helicopter transportation planning.